PENGARUH KONSENTRASI AWAL LARUTAN ION LOGAM Cr+6 TERHADAP PENYERAPAN BIOMASSA ALGA HIJAU (Mougeotia sp.) YANG DIMODIFIKASI dengan METANOL - Hervi Karlina; Mawardi Anwar (Departemen Kimia FMIPA UNP, 2020)
Heavy metals are dangerous that can pollute the environtment and cause health problems because they are toxic and carcinogenic, one example is the metal ion Cr+6. On eway to overcome heavy metal ion in waste is the biosorption method. This research was conducted to determine the absorption capacity of green algae (Mougeotia sp.) biomass modified with methanol and determine the effect of initial concentration of the solution of Cr+6 metal ion. The result showed that the optimum absorption of Cr+6 metal ion by green algae (Mougeotia sp.) biomass modified with methanol was at concentration of 250 mg/L. The maximum absorption capacity (qm) obtained is 5,1020 mg/g. Cr+6 metal ion biosorption using green algae (Mougeotia sp.) biomass modified with methanol fulfils the Langmuir Isotherm equation with a coefficient value (R2) of 0,955.